Pembentukan Karakter Percaya Diri Siswa SDI Wahid Hasyim Pakisaji Kabupaten Malang Melalui Kegiatan Ekstrakurikuler Tari - Amin, Muhammad; Maghfiro, Lailatul (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This research is motivated by the fact that the extracurricular role of dance can form the confident character of SDI students Wahid Hasyim Pakisaji Malang Regency. The school states that many students need the means to accommodate the talents of student interests in order to become children who have a confident character. Therefore the extracurricular dance was held as a container of their interests and talents. And this study aims as: 1. To describe the effort to form a confident character in SDI Wahid Hasyim Pakisaji Malang Regency through dance extracurricular activities. 2. To describe the impact of dance extracurricular activities on the formation of students' self-confidence in School, Malang Regency. This study uses qualitative research types (1) Observation used to find information in the field directly the role of extracurricular (2) Interviews to find information about the extracurricular role of dance (3) documentation to look for data about dance extracurricular at SDI Wahid Hasyim Pakisaji Malang Regency. The findings of this study indicate that 1. dance extracurricular activities play a role in honing students' self-confidence character. With the existence of dance extracurricular students have a place to hone their talents and as a means of forming students' confidence. 2. The impact of dance extracurricular activities on the formation of the confident character of SDI Students Wahid Hasyim Pakisaji Malang Regency is that students' confidence becomes active and creative. Students are quick to absorb knowledge because they are not ashamed to ask questions and will be honed by their social life in school and outside school.